1999
DOI: 10.1046/j.1365-2125.1999.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of enterally administered cisapride in young infants with gastro‐oesophageal reflux disease

Abstract: Aims To investigate the pharmacokinetics of enterally administered cisapride suspension in young infants being treated for gastro-oesophageal reflux disease. Methods Plasma cisapride concentrations in 49 subjects (weight: 825-5010 g; n= 108 samples, median two per patient; concentration: 14.8-170 ng ml −1 ) were fitted to a one-compartment model with first-order absorption and elimination in the NONMEM program using a logarithmic transformation of the observed and predicted concentrations. Fitting was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…This observation is confi rmed by our data which demonstrated a signifi cant prolongation of the QTc interval in ELBW infants but not in more mature infants. In young infants, cisapride concentrations were found to be higher (up to 170 ng/ml) and to be dependent on weight [11] . Very high serum levels of cisapride, which exceeded the serum levels in adult patients (maximum 80 ng/ml) by 2-to 3-fold [17] , were found in some of our patients.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is confi rmed by our data which demonstrated a signifi cant prolongation of the QTc interval in ELBW infants but not in more mature infants. In young infants, cisapride concentrations were found to be higher (up to 170 ng/ml) and to be dependent on weight [11] . Very high serum levels of cisapride, which exceeded the serum levels in adult patients (maximum 80 ng/ml) by 2-to 3-fold [17] , were found in some of our patients.…”
Section: Figmentioning
confidence: 99%
“…One milliliter of blood was centrifuged within 30 min. Serum was frozen and stored at -20 ° C until measurements were performed by HPLC with fl uorescence detection according to the method of Preechagoon et al [11] .…”
Section: Study Protocolmentioning
confidence: 99%
“…(95-98%), concentrations of free drug can still reach the low concentration range used in this experiment (15,16). At the lowest concentration (0.03 M) used in the present study, none of the electrophysiological parameters was significantly altered.…”
mentioning
confidence: 51%
“…Population pharmacokinetics deals with limited data available from a wide range of patients and allows the development of a population model, including average pharmacokinetic parameters, covariates, and intra-and interindividual variability [19]. A previous population pharmacokinetic analysis of cisapride conducted in neonates and published before the end of our study showed that clearance was related to body weight, attesting to the relevance of a weight-based dosing regimen [20]. However, the authors did not find a role of postnatal age, although impaired metabolism could occur in this population and lead to drug accumulation.…”
Section: Introductionmentioning
confidence: 78%
“…The model described by Preechagoon et al [20] was first fitted to our data in order to evaluate its ability to describe concentrations in an independent group of neonates. Secondly, the data were analysed by nonlinear mixed effect modelling using NONMEM software (version V, level 1.0) and Visual-NM (RDPP, Montpellier, France) a Windows-based interface to NONMEM containing graphical and statistical tools.…”
Section: Population Pharmacokinetic Analysismentioning
confidence: 99%